1989
DOI: 10.1161/01.str.20.4.465
|View full text |Cite
|
Sign up to set email alerts
|

The potential role for ultrafast cardiac computed tomography in patients with stroke.

Abstract: We studied 40 patients with stroke of potential cardioembolic origin by cardiac ultrafast computed tomography and two-dimensional echocardiography. Cardiac ultrafast computed tomography was more sensitive (positive in eight of 14 instances) than two-dimensional echocardiography (positive in two of 14 instances) for the detection of intracardiac thrombus, which was found in 13 patients. Mitral anular calcification was diagnosed more often by two-dimensional echocardiography (four of five instances) than by card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…Using 2DE and UFFCT, Helgason et al 18 evaluated patients with suspected cardioembolic stroke and found a slightly higher incidence of technically difficult 2DE studies (43%) than we did (32%). Either 2DE or UFCCT detected intracardiac thrombi in 13 of the 40 patients in that series.…”
contrasting
confidence: 58%
“…Using 2DE and UFFCT, Helgason et al 18 evaluated patients with suspected cardioembolic stroke and found a slightly higher incidence of technically difficult 2DE studies (43%) than we did (32%). Either 2DE or UFCCT detected intracardiac thrombi in 13 of the 40 patients in that series.…”
contrasting
confidence: 58%
“…Cardiac ultrafast CT has higher specificity for the detection of ventricular thrombi than two-dimensional echocardiography. 62 However, the need for contrast material is a disadvantage, and one cannot perform serial bedside examinations. Finally, the ultrafast CT systems are not widely available at this time.…”
Section: Left Ventricular Thrombimentioning
confidence: 99%
“…Only 2 out of 14 (14.3%) studies had a low risk of bias for all of the domains of the QUADAS-2 checklist [16,18]. Concerns regarding applicability were generally low except for the domain 'interpretation and conduct of the index-test' for which two studies scored a high concern due to using outdated CT scanners (Imatron C-100) [15,16].…”
Section: Study Qualitymentioning
confidence: 99%
“…We identified 1530 publications in the initial search, of which 42 were selected for full-length review. Of these, 14 articles fulfilled the inclusion criteria and were included in the analyses [8,[15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Study Selectionmentioning
confidence: 99%